Study of selective reduction in lateritic nickel ore: Saprolite versus limonite. (2021) - Nurjaman, Fajar; Astuti, Widi; Bahfie, Fathan; Suharno, Bambang
Abstract: Saprolite has higher basicity than limonite. The difference between magnesium and silicon oxide in lateritic nickel ore plays an important role in the selective reduction process. Therefore, in this work, the selective reduction of saprolite and limonite was carried out to reveal the effect of lateritic nickel ore basicity (MgO/SiO2 ratio) on phase transformation and microstructure of reduced nickel ore. The raw materials, such as nickel ore, bituminous coal, and sodium sulfate, were crushed into −100 mesh. It was mixed homogenously and pelletized into10-15 mm of diameter. The reduction process was carried out in a muffle furnace at 950 °C to 1250 °C for 60 min. After that, the wet magnetic separation process was conducted to the reduced ore to separate ferronickel from its gangue. The XRF was performed to analyze the iron and nickel content in concentrate and tailing, while XRD and SEM-EDS were used to identify the phase transformation and microstructure of reduced ore. The result showed a high MgO/SiO2 ratio in saprolite generates the iron-nickel-magnesium silicate, which was difficult to reduce rather than the iron-nickel oxide in limonite. Thus, saprolite generates lower nickel recovery than limonite. More additives and high-temperature reduction is required in the reduction process of saprolite for resulting high nickel recovery. While limonite, it needs more additives to obtain a high nickel grade in ferronickel.